Improving Access to Justice: Community-based Solutions. (January 2019) - Selita, Fatos
Inaccessibility to justice is a major issue internationally, and in some countries access to justice has decreased in recent years. For example, the growth of inequality and decline of state support have left access to justice in the UK and the USA in a worst state in decades. There is therefore an urgent need to find solutions to protect peoples' rights. This article outlines key issues of access to justice and identifies a number of solutions from grassroots efforts to organizational changes. The article highlights the importance of community-based solutions, such as mass pro bono contributions from individuals, law service providers and other organizations. It also proposes, as a key solution, making legal professions more representative of societies, and calls for law schools and legal regulators to take the required steps. Another important contributor to improved access to justice is promotion of pro bono work by all lawyers and law organizations at their own initiative. The article also discusses enhancing existing law degrees with additional topics on access to justice, to help students gain an objective picture of the realities of the legal system, and on individual differences, to benefit from latest interdisciplinary science. Community-based solutions provide stability even in times of difficult economic circumstances and political turbulence, and therefore are relevant to all societies.